Emotive aspect of language and speech (based on the modern Belarusian language) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2017)
The article deals with topical issues of linguistics of emotions as one of the most important trends in modern linguistics. The first concept of linguistics of emotions on the material of the Russian language was proposed by V. Shakhovsky. The priority directions, achievements and tasks of emotiology are indicated. Emotiveness is regarded as a functional-semantic category which has a field structure. The category of emotiveness includes the multilevel units of the language (phonetic, lexical, grammatical) that have an emotive meaning and emotive function. The functional-semantic field of the category of emotiveness consists of the center and the periphery. The center of the field is occupied by pure emotives which have only an emotive meaning. The periphery of the field is occupied by potential emotives which have an emotive meaning created by the situation of communication.  Lexical and syntactic language and speech emotives are described on the material of the modern Belarusian language. Language lexical emotives in the Belarusian language are represented by affectives and connotatives. Affectives have only an emotional meaning, for connotatives emotive meaning is a connotation, an emotive evaluative seme. Speech lexical emotives are words that acquire an emotional meaning in the context, in the language they are emotionally neutral words. Language syntactic emotives are represented by emotional syntactic patterns of sayings that are stable grammatical schemes. Syntactic emotives are supplemented with emotionally charged utterances in speech. This colour is created by intonation or emotive markers, which are particles. Particles create an emotive frame of saying. The differentiating characteristics of emotive sayings and emotionally charged utterances are determined by their communicative aim: emotionally charged utterances convey emotional reports, questions, stimuli, wishes while emotive sayings directly express the speaker’s feelings and emotions.
Keywords: linguistics of emotions; emotiology; the category of emotiveness; emotive; lexical emotive; syntactic emotive